RANCANG BANGUN DAN UJI COBA MODUL/E-MODUL TEMATIK INTERAKTIF BERBASIS PROFIL PELAJAR PANCASILA DI SDN 151 INPRES KALAMPA KABUPATEN TAKALAR: - - Riswanto; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop an interactive thematic module/e-module based on the Pancasila Student Profile to improve learning quality at SDN 151 Inpres Kalampa. The background of this study is the need for innovative teaching materials that are contextual, interactive, and aligned with the Merdeka Curriculum. The method used is Research and Development (R&D) which includes needs analysis, design, multimedia integration, validation, and trials. The results show that the developed module is valid and practical. Trial results indicate that 80% of students found the module easy to understand and use. The module effectively increases student motivation, reinforces concept understanding, and integrates the values of the Pancasila Student Profile. In conclusion, this innovation improves teacher professionalism in digital pedagogy and student learning quality.